Highly efficient and air stable thermoelectric devices of poly(3-hexylthiophene) by dual doping of Au metal precursors. (April 2021) - Kang, Young Hun; Ko, Seo-Jin; Lee, Min-Hye; Lee, Young Kuk; Kim, Bumjoon J.; Cho, Song Yun
Abstract: The electrical conductivity and doping stability of poly(3-hexylthiophene) (P3HT) in ambient air are significantly improved using a gold chloride dopant, where the coexistence of AuCl4 − and Au nanoparticles contributes to high electrical conductivity and doping stability at the same time. The uniformly formed Au nanoparticles induce a facile charge transfer in a thin film of AuCl3 -doped P3HT as examined by the crystallography and transmission electron microscopy. P3HT doped with AuCl3 exhibits a high electrical conductivity of 207 S cm − 1, a Seebeck coefficient of 73.9 μV K − 1, and an optimized power factor of 110 μW m −1 K −2 . Importantly, AuCl3 -doped P3HT shows excellent air stability. After exposure to the ambient condition for 300 h, the optimized power factor of the AuCl3 -doped P3HT maintains over 80% of the initial, whereas that of the FeCl3 -doped P3HT decreases to only 20% of the original. Finally, a flexible and organic thermoelectric generator (OTEG) is fabricated using the AuCl3 -doped P3HT by slot-die coating. The OTEG shows a relatively high open-circuit voltage ( V oc ) of 7.96 mV and a short-circuit current ( I sc ) of 0.93 μA, resulting in a power density of 18.5 nW cm − 2 at a temperature gradient of 10 °C. Graphical Abstract: Highly improved thermoelectric performance and doping stability of poly(3-hexylthiophene) by dual doping effect ga1 Highlights: Thermoelectric (TE) performance and doping stability of Poly(3-hexylthiophene) are highly improved. A gold chloride with two different chemical states in the form of AuCl4− and Au nanoparticles enhances doping effect. A flexible TE generator with high durability is successfully demonstrated.